The Influence Of Product Diversity, Shopping Experience, And Service Quality On Consumer Purchase Decisions At Bumdes Krowe Stores - Fahmi Pradipta Tama; Siti Chamidah; Adi Santoso (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2023)
Village Owned Enterprises (BUMDES) are institutions established with the aim of improving the welfare of society through the development of productive economic enterprises and other sectors. Village Owned Enterprises (BUMDES) are growing over time with various new innovations that have been implemented to attract community interest. This study aims to determine the effect of product diversity, shopping experience, and service quality on consumers' repurchase decisions at BUMDES Krowe stores. The research method used is a quantitative method using primary data and secondary data. The data analysis method used is instrument test, multiple linear regression analysis, coefficient of determination, t test, and F test. The results show that: (1) product variety partially has a significant effect on repurchase decisions. This shows that the availability of a variety of products will increase repurchase decisions. (2) shopping experience partially has a significant effect on repurchase decisions. This shows that a good shopping experience will increase repurchase decisions. (3) service quality partially has a significant effect on repurchasing decisions. This shows that the existence of optimal service quality will increase repurchase decisions. (4) product variety, shopping experience, and service quality simultaneously affect repurchase decisions. These three variables have an important role in influencing repurchase decisions, where the availability of a variety of products, a good shopping experience, and optimal service quality will jointly influence repurchase decisions.